Perkembangan Islam di Kerajaan Bone Sulawesi Selatan, Indonesia pasca Musu' Selleng - Sahrul, Rahmawati Harisa (2017)
This research discusses the history and development of Islamisation in the Regency of Bone, South Sulawesi from 1611 to the present. Unlike the rest of the region which saw the spread of Islam conducted in a peaceful manner, the situation in the Regency of Bone was anything but peaceful, it was instead spread through wars known as Musu’ selleng, conducted by the kingdom of Gowa. This research was conducted using a qualitative approach, focusing on library research. The main reference being the lontara scripts which contain local historical records of the Goverment of Bone. Using the historical approach (Dirasat tārīkhiyyah) in exposing the reality of Islamisation in the Regency of Bone from 1611 until the present, it is essentially the study of historical sources, the implementation of the level of activities including its historical method, namely: Heuristics (collecting traces of the past); criticism of source (investigate whether the historical traces are authentic, both form and contents); interpretation (set of interrelated meanings of facts obtained) and the presentation i.e. delivering the synthesis obtained in the form of a story and presentation or historiography. This study argues that the causes that encourage the war known as Musu' Selleng in the process of Islamisation of the government of Bone, is a "direct cause" while the "indirect cause" is the desire of the Government of Gowa, to make it a strong government, both economically and politically. This study found that the Government of Bone was defeated which meant that the King of Bone had to accept Islam on 23 November 1611. The study also highlights the role played by the Kingdom of Bone in spreading Islam which in the beginning was rejected but spread quickly and became the official religion of the region. This research, which looks at the spread of Islam in the Regency of Bone until the present, is expected to provide additional understanding about the process of islamisation in the Kingdom of Bone, conducted through the wars known as Musu’ selleng.